Predicting counselor candidates’ altruism in Türkiye: The role of wellness, mindfulness, and gender - Akgündüz, Ece Yağcı; Atik, Gökhan (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study aimed to assess how well the wellness, mindfulness, and gender of counselor candidates could predict their level of altruism. A total of 357 senior students from Guidance and Psychological Counseling programs across 18 universities in various Turkish cities participated. The data were collected using the Personal Information Form, Altruism Scale, Well-Star Scale, and Mindfulness Scale. The results of the multiple linear regression analysis indicated that these variables collectively explained 24% of the variance in altruism. Wellness and gender emerged as significant predictors of altruism among the candidates, with wellness being the strongest predictor. Notably, wellness was positively associated with altruism, and female candidates scored higher in altruism than their male counterparts. However, mindfulness did not significantly influence the prediction of altruism. The study’s results were examined in the context of the literature, and recommendations for counselor educators and researchers were provided based on these findings.